The Image of Colour and Number in Fairy Tales: The Case of Bolu Folk Tales - Kaplan, Haktan; Peker, Selçuk (Journal of Education Culture and Society, 2023)
Aim. How the concepts of colour and number in Bolu tales are perceived in the beliefs and lives of cultures has been examined in our study. We tried to find an answer to the importance of colour and number images in Turkish culture, to compare them with literary works in the literature, in what sense these images are used and whether there is a fundamental point in these areas of use.Methods. In this study, the method of literature review, which is one of the qualitative research techniques, was used. Various researches previously discussed on this subject were also used as auxiliary elements.Results. Since the scope of our study is within certain limits, common colours, and numbers, which are more common in Turkish culture, are discussed. The white, black, green, and yellow colours are detected in Bolu tales; the numbers three, seven and forty carry the meanings assigned to them in Turkish culture and Islam.Conclusion. This study, the use of colours and numbers in fairy tales was examined in Bolu tales and a generalisation was reached. As a result of the colours and numbers being images in the 88 fairy tales examined, the colours and numbers determined in the tales were handled from a historical, religious and cultural point of view; first of all, explanations were made about the meaning of the concepts of colour and number and how they existed, and it was determined in which context of meaning the explanations were reflected imaginatively in Bolu tales.